基于SolidWorks的变速箱变速机构模态分析 - 左晓明 (Jixie chuandong)
A farm vehicle gearbox is chosen as research object,and the 3D model of gearbox shift mechanism is firstly built up by using SolidWorks software.The Simulation module is utilized for modal analysis of shift mechanism by using finite element method.The modal forms of shift mechanism under several frequencies are gained.A reference for reverse engineering and optimization design of shift mechanism is provided.